Key conservation actions for European steppes in the context of the Post-2020 Global Biodiversity Framework - Cristian Pérez-Granados; Ana Benítez-López; Mario Díaz; João Gameiro; Bernd Lenzner; Núria Roura-Pascual; Julia Gómez-Catasús; Rocío Tarjuelo; Adrián Barrero; Luis Bolonio; Gerard Bota; Mattia Brambilla; et al. (Sustainability Science, 2025)
The Kunming–Montreal Global Biodiversity Framework (KM–GBF) envisions a world living in harmony with nature by 2050, with 23 intermediate targets to be achieved by 2030. However, aligning international policy and national and local implementation of effective actions can be challenging. Using steppe birds, one of the most threatened vertebrate groups in Europe, as a model system, we identified 36 conservation actions for the achievement of the KM–GBF targets and we singled out—through an expert-based consensus approach—ten priority actions for immediate implementation. Three of these priority actions address at least five of the first eight KM–GBF targets, those related to the direct causes of biodiversity loss, and collectively cover all the targets when implemented concurrently. These actions include (i) effectively protecting priority areas, (ii) implementing on-the-ground habitat management actions, and (iii) improving the quality and integration of monitoring programmes. Our findings provide a blueprint for implementing effective strategies to halt biodiversity loss in steppe-like ecosystems. Our approach can be adapted to other taxonomic groups and ecosystems and has the potential to serve as a catalyst for policy-makers, prompting a transition from political commitment to tangible actions, thereby facilitating the attainment of the KM–GBF targets by 2030.